2006
DOI: 10.1090/s0002-9947-06-04347-9
|View full text |Cite
|
Sign up to set email alerts
|

Functions of bounded variation, the derivative of the one dimensional maximal function, and applications to inequalities

Abstract: Abstract. We prove that if f : I ⊂ R → R is of bounded variation, then the uncentered maximal function Mf is absolutely continuous, and its derivative satisfies the sharp inequality DM f L 1 (I) ≤ |Df |(I). This allows us to obtain, under less regularity, versions of classical inequalities involving derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 11 publications
1
104
0
Order By: Relevance
“…Tanaka [ 14 ] first proved that is weakly differentiable and satisfies if . The above result was later refined by Aldaz and Pérez Lázaro [ 15 ] who showed that if f is of bounded variation on , then is absolutely continuous and where denotes the total variation of f . The above result directly yields ( 1.1 ) with constant (see also [ 16 ]).…”
Section: Introductionmentioning
confidence: 95%
“…Tanaka [ 14 ] first proved that is weakly differentiable and satisfies if . The above result was later refined by Aldaz and Pérez Lázaro [ 15 ] who showed that if f is of bounded variation on , then is absolutely continuous and where denotes the total variation of f . The above result directly yields ( 1.1 ) with constant (see also [ 16 ]).…”
Section: Introductionmentioning
confidence: 95%
“…This question was investigated by Luiro and later extensions were given in . More interesting works related to this topic may be found in .…”
Section: Introductionmentioning
confidence: 99%
“…Since we do not have sublinearity for the weak derivatives of the Hardy-Littlewood maximal function, the continuity of M : W ,p (R n ) → W ,p (R n ) for < p < ∞ is a rmatively a nontrivial issue, which was addressed by Luiro [23] and later extensions were given in [24]. We can consult [2,4,5,7,25,26] for the endpoint Sobolev regularity of maximal operators, as well as [17,20] for the regularity properties of maximal operators on other smooth function spaces, such as Triebel-Lizorkin spaces, fractional Sobolev spaces and Besov spaces. It should be pointed out that the commutativity with translations for maximal operators plays a key role in deducing the boundedness of maximal operators on W ,p (R n ).…”
Section: Introduction Backgroundmentioning
confidence: 99%